2017
DOI: 10.17576/pengurusan-2017-51-04
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effects of Independent Directors’ Human Capital on the Relationship between Related Party Transactions and Firm Performance: Evidence from Malaysia

Abstract: The purpose of this study is to examine the effect of related party transactions (RPTs) on firm performance and whether this effect is moderated by independent directors' (INEDs) presence and their human capital (i.e. functional and firmspecific knowledge). Based on a sample of 300 non-financial firms listed on Bursa Malaysia for 2013, this study found that RPTs in general, have a positive effect on firm performance and this effect varies according to the parties involved in RPTs. Specifically, this study foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
3
0
3
Order By: Relevance
“…Pendedahan urus niaga pihak berkaitan (UPB) telah mendapat perhatian badan penggubal piawaian perakaunan berikutan berlakunya banyak skandal perakaunan membabitkan UPB. Memandangkan UPB berpotensi digunakan untuk dua tujuan berbeza iaitu untuk kepentingan pihak dalaman syarikat yang oportunis (Rahmat et al 2021;Agnihotria & Bhattacharya 2019;Kohlbeck & Mayhew 2010) atau untuk tujuan perniagaan yang sah (Md. Nor & Ku Ismail 2017;Ryngaert & Thomas 2012), maka Malaysian Financial Reporting Standards (MFRS) 124 Related Party Disclosures telah diterbitkan dalam tahun 2011 untuk memastikan urus niaga ini dilaporkan dengan sewajarnya.…”
Section: Pengenalanunclassified
See 1 more Smart Citation
“…Pendedahan urus niaga pihak berkaitan (UPB) telah mendapat perhatian badan penggubal piawaian perakaunan berikutan berlakunya banyak skandal perakaunan membabitkan UPB. Memandangkan UPB berpotensi digunakan untuk dua tujuan berbeza iaitu untuk kepentingan pihak dalaman syarikat yang oportunis (Rahmat et al 2021;Agnihotria & Bhattacharya 2019;Kohlbeck & Mayhew 2010) atau untuk tujuan perniagaan yang sah (Md. Nor & Ku Ismail 2017;Ryngaert & Thomas 2012), maka Malaysian Financial Reporting Standards (MFRS) 124 Related Party Disclosures telah diterbitkan dalam tahun 2011 untuk memastikan urus niaga ini dilaporkan dengan sewajarnya.…”
Section: Pengenalanunclassified
“…Nor dan Ku Ismail (2017), Kohlbeck dan Mayhew (2010) serta Gordon et al (2004), UPB boleh memberi dua kesan berbeza iaitu kesan positif (dari perspektif urus niaga cekap) atau kesan negatif (dari perspektif konflik kepentingan). UPB dianggap urus niaga cekap kerana dapat membantu syarikat mengurangkan kos urus niaga, bertindak balas terhadap ketidaktentuan persekitaran, penggunaan aset yang lebih cekap, mempercepatkan proses pertukaran kontrak, penyelarasan strategi dan perolehan kepakaran daripada pihak berkaitan (Md Nor & Ku Ismail 2017;Ryngaert & Thomas 2012;Jian & Wong 2010;Ge et al 2010). Oleh sebab itu, perlaksanaan UPB dalam sesebuah perniagaan khususnya yang melibatkan syarikat dan kumpulan sudah menjadi tidak asing lagi dan banyak syarikat menjalankan urus niaga dengan syarikat dalam kumpulan seperti subsidiari, bersekutu atau usahasama bagi memenuhi objektif syarikat kumpulan.…”
Section: Pengenalanunclassified
“…2022, 15, x FOR PEER REVIEW 10 of Pengurusan that discusses the determinant of firm performance among SMEs in Malays Their study found that the performance of SMEs is affected by entrepreneurial orientatio innovation capability, and knowledge creation. Subsequently, a study on firm performan was performed by Nor and Ismail (2017) and Abdullah and Shukor (2017). The study by N and Ismail ( 2017) is in the finance domain, positing that the firm performance of non-financ companies listed on Bursa Malaysia was affected by related party transactions (RTPs).…”
Section: Trend Topicsmentioning
confidence: 99%
“…The human capital theory postulates an accumulation of personal stocks of education, skills, and experience in heightening cognitive and productive capabilities that bring benefit to both the individual and their organization (Becker, 1964;Terjesen et al, 2009). These human capital capabilities often classified as functional and firmspecific knowledge enable independent directors to perform their monitoring and advising role effectively (Nor and Ismail, 2017). Thus, women who accumulate wide stocks of human capital will be considered for directorships (Kesner, 1988;Terjesen et al, 2009).…”
Section: Human Capital Theorymentioning
confidence: 99%